Nanosecond Pulses Generation With Rose Gold Nanoparticles Saturable Absorber - Harun, S W; Abdul Latiff, Anas; Rosol, A H A; Abdul Khudus, M I M (Indian Association for the Cultivation of Science (IACS), 2019)
We demonstrate a mode-locked nanosecond erbium-doped fiber laser using gold nanoparticles saturable absorber. The gold nanoparticles were obtained through sodium borohydrate reduction method and made into a film structure by embedding into poly (vinyl alcohol). The laser directly produces nanosecond pulses with stable mode locking at a pump threshold of 157 mW. Resultant output pulses have central wavelength, pulse duration and repetition rate of 1561 nm, 436 ns and 1 MHz, respectively. The average output power was measured to be 6.94 mW under the pump power of 245 mW, corresponding to single pulse energy of 6.8 nJ. The experimental results show that gold nanoparticles are a promising material for ultrafast laser systems.